The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/hsc.13291
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and knowledge of antenatal care among pregnant women

Abstract: Health literacy has a direct impact on pregnancy from the perspectives of both the mother and the baby. This study aimed to determine the level of health literacy and assess the knowledge of antenatal care among pregnant women. From among all pregnant women who presented to the hospital's obstetric polyclinic during the study's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
4
9
0
1
Order By: Relevance
“…Health literacy (HL) skills enable women to access necessary sources of information, filter that information and apply it to their situations for a maximum benefit to their health (Lori et al, 2015). Research indicates that pregnant women with better HL skills have more positive health behaviours such as planned pregnancy, earlier antenatal follow-ups, regular antenatal care, regular use of folic acid, iron preparations, breastfeeding self-efficacy during pregnancy and exclusive breastfeeding for the first 6 months (Asadi et al, 2020;Astantekin et al, 2019;Guler et al, 2021;Senol et al, 2019). Pregnant women with poor HL skills who cannot access or understand health information are a major concern because women are usually the primary agents to improve the health of their children and families (Charoghchian Khorasani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy (HL) skills enable women to access necessary sources of information, filter that information and apply it to their situations for a maximum benefit to their health (Lori et al, 2015). Research indicates that pregnant women with better HL skills have more positive health behaviours such as planned pregnancy, earlier antenatal follow-ups, regular antenatal care, regular use of folic acid, iron preparations, breastfeeding self-efficacy during pregnancy and exclusive breastfeeding for the first 6 months (Asadi et al, 2020;Astantekin et al, 2019;Guler et al, 2021;Senol et al, 2019). Pregnant women with poor HL skills who cannot access or understand health information are a major concern because women are usually the primary agents to improve the health of their children and families (Charoghchian Khorasani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple studies have found that pregnant women struggle to understand health information [33][34][35][36]. In our study, participants struggled to align their behaviour with their health knowledge, suggesting that adequate knowledge about health does not necessarily impact the women's behaviour.…”
Section: A Need For Clear and Specific Action-oriented Knowledgementioning
confidence: 66%
“…However, multiple studies have found that pregnant women struggle to understand health information (32)(33)(34)(35). In our study, participants struggled to align their behaviour with their health knowledge and lacked support from health professionals.…”
Section: Discussionmentioning
confidence: 84%